Bioactive Organocopper Compound from Pseudomonas aeruginosa Inhibits the Growth of Xanthomonas citri subsp. citri - de Oliveira, Admilton G.; Spago, Flavia R.; Simionato, Ane S.; Navarro, Miguel O. P.; da Silva, Caroline S.; Barazetti, André R.; Cely, Martha V. T.; Tischer, Cesar A.; San Martin, Juca A. B.; de Jesus Andrade, Célia G. T.; Novello, Cláudio R.; Mello, João C. P.; et al. (Frontiers in Microbiology, 2016)
Citrus canker is a lot destructive disease of citrus species. The challenge is to find new compounds that show strong antibiotic activity, low toxicity to plants and the environment. The objectives of the present study are (1) produce, purify and evaluate the antibiotic activity of secondary metabolites produced by induction by P. aeruginosa LV strain in vitro against Xanthomonas citri subsp. citri (strain 306), (2) study the potential for semi-purified secondary metabolites on foliar application to control citrus canker under greenhouse conditions, (3) identify the antibiotic activity in orange leaf mesophyll infected with strain 306 by electron microscopy. Two pure bioactive compounds were isolated, organocopper antibiotic compound and phenazine-1-carboxamide. The phenazine-1-carboxamide did not show any antibiotic activity under the experimental conditions used in this study. The organocopper antibiotic compound showed a high level of antibiotic activity with a minimum inhibitory concentration of 0.12 µg mL-1. In greenhouse tests for control of citrus canker in orange trees, the semi-purified fraction F3d, reduced lesion formation about 97%. The concentration used was five hundred times lower than recommended commercial product of metallic copper-based. Electron microscopy showed that F3d altered the exopolysaccharide matrix and causing cell lysis of the pathogen inside the citrus canker lesions. These results suggest that secondary metabolites produced by induction by P. aeruginosa LV strain has a high potential to be used as a bioproduct to control citrus canker.